Implementing of Integrated Public Transport Services – Examples of Budapest Transport Association - Denke, Zs. (Acta Technica Jaurinensis, 2011)
This paper describes how integrated public transport system was already implemented in Hungary. The integrated public transport system organiser in Budapest agglomeration and its activity is shortly introduced. Integration of public transport system on service, tariff and information level is analysed in examples of Budapest Transport Association.